Relación entre los impuestos sobre la renta empresarial y la inversión extranjera directa en los países de América Latina: panel de datos 1990 – 2015 (2020)
This paper presents the results of an investigation about the relation between corporate income taxes and foreign direct investment in Latin American countries, contributing to the expansion of the empirical heritage in terms of foreign direct investment and its determinants in a crucial period of time for the economic history of the region (1990 - 2015), through the application of econometric models for panel data. As a result of the econometric results, it is inferred that macroeconomic variables such as GDP growth, the degree of Commercial Opening, regulatory quality and the qualification of the workforce have a greater preponderance in investment decisions, realizing that those countries that show a positive economic growth, a greater facility for foreign trade, a reliable government structure and a qualified human resource, they are the most desirable for investment.